2018
DOI: 10.4049/jimmunol.1701586
|View full text |Cite|
|
Sign up to set email alerts
|

Regulation of the DNA Repair Complex during Somatic Hypermutation and Class-Switch Recombination

Abstract: B lymphocytes optimize Ab responses by somatic hypermutation (SH), which introduces point mutations in the variable regions of the Ab genes and by class-switch recombination (CSR), which changes the expressed C region exon of the IgH. These Ab diversification processes are initiated by the deaminating enzyme activation-induced cytidine deaminase followed by many DNA repair enzymes, ultimately leading to deletions and a high mutation rate in the Ab genes, whereas DNA lesions made by activation-induced cytidine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
2
8
1
Order By: Relevance
“…Thus, the ChIP sequencing data support that the increases in protein interactions of ETS1 obtained in PLA and co‐IP are coupled to SH/CSR. The increase in localisation of ETS1 at Sμ and Sγ1 upon SH/CSR is in agreement with the reported increases in localisation of E2A and PAX5 at Sμ and Sγ1 .…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Thus, the ChIP sequencing data support that the increases in protein interactions of ETS1 obtained in PLA and co‐IP are coupled to SH/CSR. The increase in localisation of ETS1 at Sμ and Sγ1 upon SH/CSR is in agreement with the reported increases in localisation of E2A and PAX5 at Sμ and Sγ1 .…”
Section: Discussionsupporting
confidence: 91%
“…BCR stimulation for 0.5 h or 3 h rapidly increased localisation of E2A and PAX5 at both the Sμ and Sγ1 switch region . In contrast, here we found that BCR stimulation for 0.5 h or 3 h reduced the localisation of ETS1 at both switch regions.…”
Section: Discussioncontrasting
confidence: 79%
See 3 more Smart Citations